[Image 66] - Smith, Captain Sir William [?ob. 1732] (My University, 1802)
Captain Sir William Smith was in the Royal Engineers.
Original drawings and paintings of Ireland and Scotland, vol 1
Extensive and accurate view of the Giant's Causeway on the coast of the county of Antrim drawn on the spot by Captain Sir William Smith in 1802.
Keywords: Fortification; Architectural drawings; Ireland -- Antiquities -- Pictorial works; Giant's Causeway (Northern Ireland); Antrim (Northern Ireland : County) -- Pictorial works; Landscapes (Representations) 1800-1810